Structural features of speech activity in the context of communication theory (Eurasian Journal of Philology Science and Education, 2019)
The article deals with the problem of interaction between the process of communication and speechactivity in the context of an interdisciplinary approach. It is argued that communication and communication should be distinguished, despite the fact that these concepts are used as synonymous. Communication includes any communication, interaction of both systems and individuals and includes allkinds of communication. The content of communication is the exchange of information. Language andspeech activity are included in the process of communication, but they are historical, not modern basisof communication. It is argued that interpersonal communication as communication from «one personto another» is currently only part of the social communication process. It mediates joint activities in theimmediate microenvironment of the individual. In this regard, there is a need to identify the structuralfeatures of speech activity that determine the effectiveness of the communication process. The purposeof the article is to identify the components of speech activity that determine its structure and specificityin the context of communication theory and communicative approach.